Death Anxiety Among Nursing Students After the February 6 Türkiye Earthquake: The Role of Earthquake Fear and Religious Coping - Seher Çevik Aktura; Semiha Dertli; Askeri Çankaya (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This study was conducted to examine the mediating role of religious coping in the effect of earthquake fear on death anxiety among nursing students affected by the 6 February earthquakes.Methods: This descriptive and correlational study was conducted with 465 nursing students affected by the 6 February Earthquake. Research data were collected online via email and social networking sites (WhatsApp, Facebook, etc.) between 2 October and 1 December 2023. Data were obtained using the "Participant Introduction Form", "Earthquake Fear Scale", "Death Anxiety Scale" and "Religious Coping Styles Scale". The mediating role of religious coping in the effect of earthquake fear on death anxiety was assessed using path analysis.Results: It was observed that earthquake fear had a significant and positive effect on positive religious coping (β=0.126, p=0.006) and that earthquake fear significantly increased death anxiety (β=0.486, p<0.001). In contrast, the effect of earthquake fear on negative religious coping (β=0.087, p=0.059) and the effects of positive or negative religious coping on death anxiety (positive: β=0.000, p=0.995; negative: β=0.065, p=0.115) were not statistically significant.Conclusions: This study provides evidence for the development of educational programmes aimed at enhancing students' psychological resilience in disaster situations by revealing the effects of earthquake fear on death anxiety and religious coping among nursing students. Furthermore, the findings guide the planning of clinical interventions that support nurses' coping strategies for traumatic experiences and the integration of psychosocial support and religious coping skills into educational curricula.